PERMO-TRIASSIC PALYNOLOGY OF THE WEST TIMOR - Eko Budi Lelono; L. Nugrahaningsih; Dedi Kurniadi (Testing Center for Oil and Gas LEMIGAS, 2016)
Fifteen surface samples were examined to analyze palynology of the Permo-Triassic sediments of West Timor. The studied samples were collected from the clastic sediment of Bisane Formation which is considered to be the oldest formation. It derives from the Australian continent (Gondwana) following thecollision with the Banda volcanic arc. The Bisane Formation generally comprises thick calcareous sandstone (0.3-5 meters) with shale alternation and abundant marine microfossil of Chrinoid. The appearance of Chrinoid may indicate Permian age and shallow marine environment. Meanwhile, other Bisane sediment shows different lithology in which it is composed of the intercalation of non-calacreous, dark gray to black shale and siltstone showing papery structure and rich in sulphur. Generally, palynological assemblage of the studied samples characterises Permo-Triassic age as indicated by the existence of common striate-bisaccate pollen including Protohaploxypinus samoilovichii, P. fuscus, P. goraiensis, Striatopodocarpidites phaleratus, Pinuspollenites globosaccus and Lunatisporites pellucidus. However, the appearance of trilete-monosaccate spores of Plicatipollenites malabarensis and Cannanoropollis janakii within the non-calcareous shale samples de􀂿 nes the age as Permian or older for these samples. Interestingly, marine dino􀃀 agellates appear to mark calcareous samples suggesting the in􀃀 uence of a marine environment. They disappear from the non-calcareous samples indicating a freshwater environment. By integrating this palynological analysis and Permian tectonic event which is marked by rifting, it can be interpreted that the non-calcareous samples were formed during early syn-rift as evidenced by the occurrence of freshwater deposit (may be lacustrine). Subsequently, following sea level rises during post rift, the depositional environment shifted to shallow marine as indicated by the existence of calcareous Permo-Triassic samples. If this is the case, the appearance of Permo-Triassic sediments provides an opportunity to 􀂿 nd a new petroleum system in the Paleozoic series of West Timor. Source rock is represented by black shale, whereas reservoir is represented by thick sandstone.